Economic analysis of biomethane and bioelectricity generation from biogas using different support schemes and plant configurations. (August 2015) - Budzianowski, Wojciech M.; Budzianowska, Dominika A.
Abstract: Commercial renewable energy projects are sensitive to policy instruments that shape the rate of deployment of renewables and affect their technological evolution. This study evaluates the economic performance of biogas projects under policy involving two novel instruments: (i) BFP (biomethane feed-in premium) and CMP (carbon mitigation premium) able to shape economic attractiveness and future technological evolution of biogas. The study reveals that only conventional biogas CHP plants are likely to be profitable under current policies. Biomethane plants require incentives e.g. from BFP, but interestingly the sufficient incentive can be more than 50% lower than the current incentive for electricity. The study also finds that innovative pressurised anaerobic digestion that can achieve direct carbon intensity of 13 tCO2 per GWhf (compared with about 168 tCO2 per GWhf for conventional biogas upgrading) can be very economically attractive, if policy combining BFP and CMP is implemented. The total support required from governments under the policy combining BFP and CMP instruments is similar or even lower than that currently available for bioelectricity. In addition, carbon mitigation benefits are achieved. Policy instruments and technological innovations are therefore critical for ensuring high energy outputs from biogas at a minimal economically justified carbon footprint. Highlights: BFP and CMP can shape economic viability and future technological evolution of biogas. Innovations can raise energy output and minimise carbon footprint of biogas. Incentives needed by biomethane plants can be 50% lower than these for electricity. Pressurised anaerobic digestion has direct carbon intensity of about 13 tCO2 per GWhf .